2008
DOI: 10.1111/j.1365-2702.2008.02344.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising spirituality and religion for healthcare

Abstract: Constructing adequate conceptualisations of spirituality and religion for clinical practice entails grounding them in the wealth of centuries of philosophical and theological thinking, ensuring that they represent the diverse society that nursing serves and anchoring them within a moral view of practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 42 publications
1
98
0
10
Order By: Relevance
“…A significant contributor to the unease with which spirituality is addressed within the health service is the echo of its origins in a religious and classicalphilosophical world which healthcare providers do not necessarily know or share (see Paley 2008b;Pesut et al 2008). It carries implications of a distinct 'spirit' in each human being which resists empirical or quantitative study, and therefore does not sit well in an evidence-based professional culture.…”
Section: Introductionmentioning
confidence: 97%
“…A significant contributor to the unease with which spirituality is addressed within the health service is the echo of its origins in a religious and classicalphilosophical world which healthcare providers do not necessarily know or share (see Paley 2008b;Pesut et al 2008). It carries implications of a distinct 'spirit' in each human being which resists empirical or quantitative study, and therefore does not sit well in an evidence-based professional culture.…”
Section: Introductionmentioning
confidence: 97%
“…Increasingly, the term spirituality is used to refer to existential and experiential pursuits pertaining to religious or spiritual values and beliefs, whereas religion refers specifically to the institutional contexts in which those values and beliefs are enacted (Larson et al 1998;Pesut et al 2008;Sawatzky et al 2005). Accordingly, Wagener and Newton Malony suggested that, within the context of adolescent development, spirituality pertains to "the essential potentiality for addressing the ultimate questions" and involves "experiences of transcendence, good and evil, belonging and connectedness, meaning and purpose" (Wagener and Newton Malony 2006, p. 139).…”
Section: Introductionmentioning
confidence: 99%
“…The therapists were disturbed by their own strong emotions and felt that their own education had neglected spiritual/religious training. On the other hand, Pesut et al (2008) claim that a healthy spirituality or religion will transcend itself into compassion; recognize the unavoidability of suffering; seek to rectify that suffering at the individual and public levels; make room for difference while searching for commonality; and decline to reduce the discourse to a search for personal, political, and economic gain. Fredriksson and Lindström (2002) revealed that if psychiatric patients could answer the why-question in suffering, they also could interpret the suffering in such a way that expansion and conciliation were made possible.…”
Section: Psychiatric Nurses' Self-rated Competence and Clinical Envirmentioning
confidence: 97%
“…It was revealed that the predictor, "years as a nurse in psychiatry" (i.e., experience), was negatively correlated to self-rated skills to attend to a patient's spiritual needs. According to Pesut et al (2008) spirituality for health care purposes must acknowledge the diverse perspectives of a globalised society. Sweden is a multicultural country with different religious beliefs as well as non-religious identities or spiritualities.…”
Section: Psychiatric Nurses' Self-rated Competence and Clinical Envirmentioning
confidence: 99%